Survey of the Level of Physical Condition of Foerza Golem Club Badminton Athletes in 2023 - Puspitaningrum, Dyah Kristi; Yuliawan, Dhedhy; Bekti, Ruruh Andayani (CV. Nusantara Sporta, 2024)
This research is motivated by observations that the physical condition of badminton athletes at Foerza Golem, Kediri Regency, is still dominated by a classical training method focused on the coach's role, leading to monotonous and less serious training sessions. The aim of this study is to assess the physical condition of Foerza Golem badminton athletes. This quantitative study involved the athletes as subjects, with physical condition tests as the instrument and percentage analysis as the method. The results showed that the right-hand strength of male athletes was categorized as